Stimulasi Kemampuan Kognitif melalui Media Kantong Emotikon pada Anak Usia Dini - Kusuma, Wening Sekar; Kusumastuti, Narendradewi; Koesmadi, Dita Primashanti (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The numeracy ability of young children is one of the important abilities for children that needs to be developed in order to equip children for the next level of education. This study aims to describe how the use of emoticon bag media can improve children's numeracy skills in group A children at Paramadinah Kindergarten Ngawi, Ngawi District, Ngawi Regency. In this study, the researcher used Classroom Action Research (CAR) which was carried out in two cycles. The subjects of this study were class A children in TK Paramadinah Ngawi, with a total of 12 students. The data collection method used in this research is observation and documentation. Children's numeracy skills at the time of pre-action can be said to have not developed. Many children have difficulty recognizing the symbols of numbers 1-10, counting the number of objects from 1-10. Children's numeracy skills can be improved through the media of emoticon bags. In the pre-action, the percentage of children's numeracy achievement was only 42% who were able to count well, in the first cycle it increased to 67% in the very well developed criteria (BSB) and in the second cycle it increased again to 83% in the very well developed criteria (BSB). So, it can be concluded that the emoticon bag media can improve the numeracy ability of group A Paramadinah Ngawi Kindergarten.